Application of Rorb Rainfall-Runoff Model to Urban and Rural Catchments - Choo, Ee Li (2004)
Over the years, many have realised the growing importance of water and its resources to sustain industrial and community development and most importantly life in all forms. However, excess of uncontrolled surface runoff could lead to flooding and potential damages in properties and loss of life. As a result, the field of hydrology and hydraulic has become a growing importance. With the current technology, various software programs are developed to assist in the analysis and study of water resources management and flood mitigation. Amongst them is the Rainfall-Runoff Routing Model which was widely used in Australia. It has also been used in some of the catchments' studies and flood mitigation projects in Malaysia, mostly to perform flood routing and estimation. The primary aim of the study is to assess the suitability of RORB model for application to catchments in Malaysia. It is used to simulate the rainfall-runoff routing process of two characteristically different catchments namely Sg Klang Basin at. Tun Perak Bridge and Sg Bernam Basin at South Kinta Consolidated Bridge. The former is highly urbanised and located in Wilayah Persekutuan while the latter is considerably rural and encompasses both Perak and Selangor states. The setting up of the model begins with subdividing the catchment into various subcatchments based on catchment topography, river system and drainage divides which are then modelled by a series of links and nodes, which represent the reaches of flow and subcatchments respectively. Next, the various input parameters such as subcatchment area and landuse condition, channel type, length and slope, fraction imperviousness, rainfall and streamflow data are defined and determined. All these are compiled in an input data file which is written in Fortran language following a specific sequence of command codes for running of the model simulations. The catchment modelling is performed up to the calibration and verification stage using 4 storm events; 2 each for calibration and verification respectively. These events are identified based on available past 3 to 40 years of rainfall and streamflow records collected from Department of Irrigation and Drainage Malaysia. The best fit model parameters, m and b, are determined and the results of the generated runoff hydrographs are compared to the observed hydrographs. The model is areally distributed, nonlinear, and has a linear or non-linear storage relationship between storage S and outflow discharge Q which is given as: S = kckrQm where kc and m are the catchment parameters determined by trial and error fitting while kr is relative delay applicable to individual reach storage calculated based on any unit of indicator of storage delay time. Two units of indicator, namely flow length and flow time, are adopted separately in 1" Model Setup and 2nd Model Setup to ascertain the sensitivity of these two units to the model and its results. This study concludes that the application of RORB model is relatively user friendly. Also, the model is less complicated in its application as it does not involve too many input parameters leading to less assumption to be made. This is an advantage in view of the inherent problem of data inadequacy and poor quality of recorded data. In addition, there are only two model parameters, m and k,, to determine because of the simplified approach to the rainfall-runoff process. The study also showed that ROD model is applicable to both urban and rural catchments. The overall results indicated variations of less than 10% between the generated and observed runoff discharges and volumes, which is of acceptable limitation. However, it is also shown SKC catchment has a higher variation than Tun Perak catchment. This is most possibly due to the fact that SKC catchment has a very much bigger catchment area about 10 times greater than Tun Perak catchment. This results in larger propagated errors or discrepancies in the modelling. But overall, the peak times and shape of the runoff hydrographs are generally matching between the observed and generated. Finally, the model is also not sensitive to the types of indicator used for relative storage delay time as the maximum variations in the results between the two model setups are 2%. In conclusion, RORB is an acceptable model which provides a reasonably good simulation of the rainfall-runoff process in a catchment